Analisis Hukum Islam Terhadap Pinjaman Uang Elektronik: (Studi Kasus Aplikasi Shopee PayLater) - Ni’matush Sholihah; Adek Nuriya; Saiful Bakhri (Cashless : Journal of Sharia Finance and Banking, 2023)
The aim of this research is to investigate the practice of Shopee PayLater among users of the Shopee application and to examine the Islamic legal perspective on the practice of electronic money lending through Shopee PayLater. This is a field research study that is descriptive in nature, and the analysis of data is conducted using a qualitative descriptive method. The findings of this research indicate that the practice of Shopee PayLater on the Shopee application involves borrowing money that is paid back in installments with varying interest rates. The due date for payment is on the 5th day of the following month after the borrowing. A late payment penalty of 5% of the amount to be paid is charged if payment is delayed. Islamic legal perspective on the practice of electronic money lending through Shopee PayLater highlights that while the Shopee PayLater practice from the Shopee marketplace already incorporates Islamic values in its transactions, it still involves riba (interest), the addition of extra charges to the principal debt, and other additional charges that burden the borrower. Additionally, there is a provision for penalties or fines for late payment, which goes against Islamic principles. These aspects of the practice should be addressed to comply with Islamic law.